Are International Students Quiet in Class? The Influence of Teacher Confirmation on Classroom Apprehension and Willingness to Talk in Class - Hsu, Chia-Fang (Sandy); Huang, I-Ting (Joyce) (Journal of International Students, 2017)
This study investigated the influence of teacher confirmation (TC) on classroom apprehension (CCA) and willingness to talk in class (WTT) among international students in the United States. The participants (N=121) completed a battery of self-report instruments online. Results confirmed a path model that TC positively predicts classroom connectedness, which in turn, positively influences self-perceived language competence, which subsequently reduces CCA and increases WTT. The influences of length of stay in the U.S. and class size were controlled in the model, while culture of origin and class type did not influence CCA and WTT. Implications of these findings were further discussed.